2008
DOI: 10.1007/s11270-008-9728-6
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Uranium by Lettuce (Lactuca sativa L.) in Natural Uranium Contaminated Soils in Order to Assess Chemical Risk for Consumers

Abstract: Uranium mining activity in Cunha Baixa (Portugal) village has left a legacy of polluted soils and irrigation water. A controlled field experiment was conducted with lettuce (Lactuca sativa L.) in an agricultural area nearby the abandoned mine in order to evaluate uranium uptake and distribution in roots and leaves as well as ascertain levels of uranium intake by the local inhabitants from plant consuming. Two soils with different average uranium content (38 and 106 mg/kg) were irrigated with non-contaminated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…The radioisotope activity data obtained in vegetables is in good agreement with previous work performed in similar geological settings (Bettencourt et al, 1988;Carvalho et al, 2009;Neves et al, 2008). The radionuclide uptake from the studied broadleaf plants (cabbage and turnip) is higher than in tubers; in the case of potatoes, analyzed with the peel, it is expected that the activity should be significantly lower if the analysis is performed without it, as it was also shown in previous studies (Neves et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…The radioisotope activity data obtained in vegetables is in good agreement with previous work performed in similar geological settings (Bettencourt et al, 1988;Carvalho et al, 2009;Neves et al, 2008). The radionuclide uptake from the studied broadleaf plants (cabbage and turnip) is higher than in tubers; in the case of potatoes, analyzed with the peel, it is expected that the activity should be significantly lower if the analysis is performed without it, as it was also shown in previous studies (Neves et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Uranium disposed into the environment can reach the top of the food chain and be ingested by humans (e.g., Anke et al, 2009;Craft et al, 2004;Neves et al, 2008Neves et al, , 2012Xie et al, 2008), causing health disorders such as kidney or liver diseases and even death (e.g., Craft et al, 2004;Xie et al, 2008). Thus, it is necessary to treat waste material containing U, as well as U-contaminated water, soil and sediment, in order to prevent its dispersion in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, during September to November (autumn season) 2005, an equal field experiment was carried out in the same Cunha Baixa soil and U concentration in lettuce was lower (100 ± 20 lg/kg FW) in soil plot irrigated with contaminated water (Neves et al 2008) than the observed in lettuce cultivated in 2006 summer season (this study). As soil conditions, namely U soil available fraction concentrations and irrigation water quality were similar, the differences in U plant leaves concentration can be explained by the lower frequency and lower amount of water irrigation used in autumn season (8 handling times, due to meteorological conditions), in opposition to 2006 summer season when plants were watered 3 and 11 times by handling and furrow, respectively (Table 1).…”
Section: Discussionmentioning
confidence: 60%
“…The soil (40 m 2 ) was divided in two plots (P1, P2) and both subdivided in four replicates each, as described in Neves et al (2008). Composite soil samples (0-20 cm) were taken at each replicate before plantation.…”
Section: Study Site and Experimental Workmentioning
confidence: 99%
See 1 more Smart Citation